DIVERSIFIKASI DAN PENGEMBANGAN PRODUK YOGURT PADA UD SUSU KAMBING ETTAWA DI DESA KARANG ANYAR KOTA LANGSA - Seprianto Seprianto; Fiddini Alham; Hartutik Hartutik; Thursina Mahyuddin; Faisal Ali Ahmad (Universitas Mataram, 2023)
In Karang Anyar Village, Langsa City, there is an ettawa goat’s milk farm that produces and sells fresh milk. From the survey conducted, the problems faced by partners are cage and animal feed problems, many consumers do not like the taste of Ettawa goat’s milk, excess production, and farm owners do not have insight into product diversification and marketing. The aims of this community service activity are to produce diversification and development of yogurt products from ettawa goat's milk. This service was carried out at UD Susu Kambing Ettawa, Karang Anyar Village, Langsa Baro District, Langsa City. The method of implementing this community service consists of the following stages: planning and preparation (team debriefing, pre-survey, determining the schedule and place of activity, preparation of tools and materials), implementation (counseling and workshops), as well as the monitoring and evaluation stage. Pretest and posttest on 15 participants were carried out to determine the level of adoption of the participants' knowledge regarding Ettawa goat milk diversification which was analyzed using the Wilcoxon Signed Test. The results of the planning and preparation stages have agreed on the tools and materials needed by the partners, the date and place of implementation, as well as the financing. The results achieved from the implementation stage were product diversification in Ettawa goat milk in the form of yogurt, packaging changes, branding (branding), and marketing using social media. The results of the monitoring and evaluation phase by administering pretest and posttest show that there are differences in the level of partner knowledge before and after counseling and workshop activities are held based on statistical tests.